Aggregation-induced emission metal organic framework, preparation method thereof and application of aggregation-induced emission metal organic framework in portable detection of low-concentration nitrobenzene
By developing the aggregation-induced luminescent metal organic framework material UiO-66-H4TCPP and its preparation method, the rapid, portable and high sensitivity problems of nitrobenzene detection in the prior art are solved, and the efficient detection of p-nitrobenzene is achieved.
Patent Information
- Application Number
- CN202510131642.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The prior art is difficult to achieve rapid, portable and highly sensitive nitrobenzene detection, especially in field detection, where there are problems of complex operation and high technical requirements.
A metal organic framework material UiO-66-H4TCPP and its preparation method were developed, and a flexible aggregation-induced luminescence film that can detect nitrobenzene gas is prepared. This material has high sensitivity and fast response fluorescence sensing performance by effectively designing organic ligands.
It realizes high sensitivity detection of p-nitrobenzene, has good aggregation-induced luminescence performance, can quickly and sensitively detect the concentration of nitrobenzene gas and solution, and has low equipment requirements and simple operation.
Smart Images

Figure CN119798702A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent sensing materials and relates to an aggregation-induced luminescent metal organic coordination polymer, and in particular to an aggregation-induced luminescent metal organic framework and a preparation method thereof and application in portable detection of low-concentration nitrobenzene. Background Art
[0002] Nitroaromatic compounds have become prominent environmental pollutants due to their potential toxicity and special explosiveness. The widespread use of nitroaromatic compounds in weapons manufacturing, metal etching and leather manufacturing industries not only pollutes groundwater, but also harms human health. Nitrobenzene (NB) is a nitroaromatic compound with high toxicity, mutagenicity and carcinogenicity. It is widely used in paint additives, pesticides and drug synthesis. Nitrobenzene can cause serious damage to human health through accumulation in water. Long-term exposure can cause anemia, leukemia, abnormal liver function and kidney disease. Due to the high volatility of nitrobenzene, the human body will experience symptoms such as nausea and vomiting after accidental inhalation, and in severe cases, it can cause damage to the lungs and nervous system. To date, a large number of conventional analytical techniques have been used to detect nitrobenzene, such as mass spectrometry, electrochemical methods, surface enhanced Raman spectroscopy, energy dispersive X-ray diffraction, etc. However, these traditional methods have some limitations and disadvantages, such as complex operation, high technical requirements for operators and difficulty in achieving rapid on-site detection. Therefore, it is necessary to develop a simple, rapid and portable nitrobenzene detection technology.
[0003] Among a series of detection methods, the fluorescence detection method has attracted extensive attention from researchers due to its advantages such as low cost, high sensitivity, fast response time, and easy portability. Among fluorescent sensing materials, the fluorescence properties of luminescent metal organic framework materials (MOFs) often depend on the fluorescence properties of their organic ligands or the fluorescence properties of their metal ions and metal clusters. Therefore, a fluorescent sensing material with specific response can be obtained by effectively designing the organic ligands of MOFs materials. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method of an aggregation-induced luminescence metal organic framework material for highly sensitively detecting nitrobenzene, the preparation method has low equipment requirements and is simple to operate; a portable flexible aggregation-induced luminescence film for detecting nitrobenzene gas is prepared on the basis of the prepared metal organic framework material; the prepared materials H4TCPP and UiO-66-H4TCPP have good aggregation-induced luminescence properties, and the materials UiO-66-H4TCPP and UiO-66-H4TCPP@PVDF film can quickly and sensitively detect nitrobenzene.
[0005] To achieve the above-mentioned purpose, the technical scheme of the present invention is as follows: an aggregation-induced emission metal organic framework, the preparation method is as follows: ZrCl4 is dissolved in an N,N-dimethylformamide solution and carried out under ultrasonic conditions, then, BDC-SO3H and AIE molecule H4TCPP are added, and then treated under ultrasonic conditions to obtain a transparent solution, a certain amount of acetic acid is added to the solution, and the mixed solution is placed in a polytetrafluoroethylene reactor for heating and reaction. After the reaction is completed, the aggregation-induced emission metal organic framework material UiO-66-H4TCPP can be obtained by centrifugal washing.
[0006] The above-mentioned aggregation-induced emission metal organic framework, the preparation method of the H4TCPP is as follows: vitamin B1 is added to a mixed solvent of CH3OH and H2O, the pH is adjusted to 9-10, 4-methyl toluate is added, the reaction mixture is stirred in an ice-water bath for 1 hour, heated to form a precipitate, and the product is obtained after filtration, acetic anhydride is added to a solution of the product and ammonium acetate, and stirred at 120°C and N2 for 12 hours to obtain a solid product, which is filtered and washed with water and diethyl ether to obtain a yellow solid 2,3,5,6-tetrakis(4-(methoxycarbonyl)phenyl)pyrazine; NaOH is added to 2,3,5,6-tetrakis(4-(methoxycarbonyl)phenyl)pyrazine in a THF-H2O solution, the mixture is refluxed for about 12 hours, tetrahydrofuran is evaporated, the pH is adjusted to 4-5, the precipitate is filtered and washed with water to obtain a yellow solid H4TCPP.
[0007] The above-mentioned aggregation-induced emission metal organic framework, the heating is heating at 60°C for 1 hour and heating at 85°C for 1 hour.
[0008] In the above-mentioned aggregation-induced emission metal organic framework, the mass ratio of BDC-SO3H to ZrCl4 is 0-0.67:1, and the mass ratio of BDC-SO3H to H4TCPP is 1:0-1.4.
[0009] In the above-mentioned aggregation-induced luminescence metal-organic framework, the heating reaction is carried out at 0-120° C. for 0-24 hours.
[0010] The above-mentioned aggregation-induced emission metal organic framework is used in the fluorescence detection of nitrobenzene in water, and the method is as follows:
[0011] 1) Add 1 mg / mL UiO-66-H4TCPP solution to a solution containing 0-200 nM nitrobenzene, and perform fluorescence test to obtain a linear relationship between nitrobenzene concentration and fluorescence intensity, y=0.04710c+1.09875, R 2 =0.99111;
[0012] 2) Add 1 mg / mL UiO-66-H4TCPP solution to the nitrobenzene solution to be tested and perform fluorescence test according to the fluorescence intensity.
[0013] Substitute it into the linear equation obtained in step 1) to calculate the concentration of nitrobenzene in water.
[0014] The above-mentioned aggregation-induced emission metal organic framework is used in the fluorescence detection of nitrobenzene gas in the following method:
[0015] 1) In a sealed container, 15 mg of UiO-66-H4TCPP powder was placed, and nitrobenzene was volatilized by heating to generate 0-50 ppm nitrobenzene gas in the device. After 20 minutes, the solid powder material was taken out and solid fluorescence test was performed to obtain the linear relationship between nitrobenzene gas concentration and fluorescence intensity, y=0.03108c+0.85508, R 2 =0.99289;
[0016] 2) Put 15 mg of UiO-66-H4TCPP powder in a sealed container, place the nitrobenzene gas to be tested in a sealed device, take out the solid powder material after 20 minutes, and perform a solid fluorescence test. The concentration of nitrobenzene gas can be calculated based on the fluorescence intensity, the linear equation obtained in step 1) and pV=nRT.
[0017] A UiO-66-H4TCPP@PVDF film for portable detection of nitrobenzene gas is provided. PVDF is added to a DMF solution, heated until the PVDF is completely dissolved, the above-mentioned UiO-66-H4TCPP powder is taken, added to the PVDF solution, stirred evenly and poured onto a glass mold, and then placed in deionized water. The UiO-66-H4TCPP@PVDF film is separated from the glass mold to obtain a UiO-66-H4TCPP@PVDF film for portable detection of nitrobenzene gas.
[0018] The above-mentioned UiO-66-H4TCPP@PVDF film that can be used for portable detection of nitrobenzene gas has a mass ratio of UiO-66-H4TCPP to PVDF of 0.2:1, and the heating reaction is carried out at 70°C for 0-30min.
[0019] The above-mentioned UiO-66-H4TCPP@PVDF film that can be used to portableally detect nitrobenzene gas is as follows: put the UiO-66-H4TCPP@PVDF film in a sealed container, and generate 0-50ppm nitrobenzene gas in the device through the thermal volatilization of nitrobenzene. After 20 minutes, take out the film, and under a 360nm ultraviolet lamp, it can be observed that the blue fluorescence of the film is effectively quenched.
[0020] The aggregation-induced emission metal organic framework material UiO-66-H4TCPP and the aggregation-induced emission flexible film UiO-66-H4TCPP@PVDF film of the present invention have the advantages of good stability, high fluorescence intensity and portability. Due to the introduction of the ligand AIE molecule H4TCPP, the material has potential application in the detection of nitrobenzene gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the synthetic route of UiO-66-H4TCPP.
[0022] Figure 2 Schematic diagram of the synthesis of AIE molecule H4TCPP.
[0023] Figure 3 This is the nuclear magnetic resonance hydrogen spectrum (1H-NMR) of the products in each step of the synthesis process of the AIE molecule H4TCPP.
[0024] Figure 4 Schematic diagram of the synthesis of the aggregation-induced emission metal-organic framework UiO-66-H4TCPP.
[0025] Figure 5 FT-IR spectra (a) and XRD spectra (b) of the AIE molecule H4TCPP, metal organic framework UiO-66-SO3H and aggregation-induced emission metal organic framework UiO-66-H4TCPP.
[0026] Figure 6 XPS spectra of the synthesized metal-organic framework UiO-66-SO3H and aggregation-induced emission metal-organic framework UiO-66-H4TCPP.
[0027] Figure 7 Fluorescence emission spectra of different ligand ratios for the synthesis of aggregation-induced emission metal-organic framework UiO-66-H4TCPP.
[0028] Figure 8 SEM images of different ligand ratios for the synthesis of aggregation-induced emission metal-organic framework UiO-66-H4TCPP.
[0029] Fig. 9 XRD spectra of different ligand ratios for the synthesis of aggregation-induced emission metal organic framework UiO-66-H4TCPP
[0030] Fig.10 This is the N2 adsorption diagram of the aggregation-induced emission metal-organic framework UiO-66-H4TCPP.
[0031] Fig.11 Thermogravimetric curve of the synthesized aggregation-induced emission metal-organic framework UiO-66-H4TCPP.
[0032] Fig.12 To characterize the aggregation-induced emission properties of the aggregation-induced emission metal organic framework UiO-66-H4TCPP, (a) and (c) are the fluorescence spectra of H4TCPP and UiO-66-H4TCPP in different aggregation states; (b) and (d) are the change curves of the fluorescence intensity of H4TCPP and UiO-66-H4TCPP in different aggregation states.
[0033] Fig.13 (a) The UV-visible absorption spectra and (b) the optimal excitation / emission spectra of the AIE molecule H4TCPP, the metal organic framework UiO-66-SO3H and the aggregation-induced emission metal organic framework UiO-66-H4TCPP.
[0034] Fig.14 The fluorescence response of the aggregation-induced emission metal organic framework UiO-66-H4TCPP to different volatile organic compounds (a) and the bar graph of its fluorescence intensity changes (b).
[0035] Fig.15 The fluorescence response of the aggregation-induced emission metal organic framework UiO-66-H4TCPP to different volatile organic compounds (0-200nM) (a) and the anti-interference test of UiO-66-H4TCPP on nitrobenzene detection (b).
[0036] Fig.16 This is the fluorescence emission spectrum of the aggregation-induced emission metal organic framework UiO-66-H4TCPP detecting 0-200nM nitrobenzene solution and the linear relationship diagram of the probe fluorescence intensity changing with the nitrobenzene concentration.
[0037] Fig.17 This is the fluorescence emission spectrum of the aggregation-induced emission metal organic framework UiO-66-H4TCPP detecting 0-50ppm nitrobenzene gas and the linear relationship diagram of the probe fluorescence intensity changing with the nitrobenzene concentration.
[0038] Fig.18 The response time and cycling performance of the aggregation-induced emission metal organic framework UiO-66-H4TCPP for nitrobenzene detection were tested.
[0039] Fig.19 Actual photos and optical photos under 365nm ultraviolet light of the flexible UiO-66-H4TCPP@PVDF film prepared by blending the aggregation-induced emission metal organic framework UiO-66-H4TCPP and polyvinylidene fluoride (PVDF) for portable detection of nitrobenzene gas.
[0040] Fig. 20This is the linear relationship between the actual photo of UiO-66-H4TCPP@PVDF film after detecting 0-50ppm nitrobenzene gas and the nitrobenzene gas concentration. DETAILED DESCRIPTION
[0041] Example 1 Aggregation-induced emission molecule H4TCPP
[0042] (a) If Figure 2 As shown, the preparation method is as follows:
[0043] Vitamin B1 (0.27 mmol) was added to a mixed solvent of CH3OH (6.00 mL) and H2O (2.00 mL), and NaOH (1.00 mL, 2 M) was added dropwise to adjust the pH to 9-10, and then methyl 4-toluate (18.29 mmol) was added. After stirring the reaction mixture in an ice-water bath for 1 hour, it was heated at 60°C for 1 hour and 85°C for 1 hour to form a precipitate. The product was obtained after filtration. Then, acetic anhydride (7.50 mmol) was added to a solution of the product (5.00 mmol) and ammonium acetate (15.00 mmol). Stirring at 120°C under N2 conditions for 12 hours gave a solid product. Filtering and washing with water and diethyl ether gave a yellow solid 2,3,5,6-tetrakis(4-methoxycarbonyl)phenyl)pyrazine (1.35 mmol).
[0044] NaOH (9.95 mmol) was added to a solution of 2,3,5,6-tetrakis(4-(methoxycarbonyl)phenyl)pyrazine (0.88 mmol) in THF-H2O (1:1, 15.00 mL), and the mixture was refluxed for about 12 hours. The tetrahydrofuran was evaporated and the solution was acidified to pH 4-5 with hydrochloric acid (2 M). The precipitate was filtered and washed with water to give H4TCPP as a yellow solid (0.81 mmol).
[0045] (II) Characterization of HDBB
[0046] For the H4TCPP NMR hydrogen spectrum test, about 10 mg of the first step product, the second step product and H4TCPP after vacuum drying were dissolved in deuterated chloroform and deuterated DMSO respectively. The test can be performed after they are completely dissolved. The test results are as follows: Figure 3 As shown, the successful synthesis of the AIE molecule H4TCPP can be proved by nuclear magnetic resonance hydrogen spectrum test.
[0047] Example 2 Aggregation-induced emission metal organic framework UiO-66-H4TCPP
[0048] (a) If Figure 4 As shown, the preparation method is as follows:
[0049] 0.106g zirconium tetrachloride (ZrCl4) was dissolved in 20mL N,N-dimethylformamide (DMF) and subjected to ultrasonication. Subsequently, 0-71.17mg 2-sulfonatoterephthalic acid (BDC-SO3H) and 50.83-122mg H4TCPP molecules were added and then treated under ultrasonication to obtain a transparent solution. The solution was mixed with acetic acid and crystallized in an oven at 120°C for 24 hours. The precipitate was separated by centrifugation, washed four times with DMF and five times with acetone. The obtained white powder was air-dried overnight and activated under dynamic vacuum at 90°C for 24 hours to obtain the aggregation-induced emission metal organic framework material UiO-66-H4TCPP. (II) Characterization of UiO-66-H4TCPP
[0050] Figure 5 FT-IR images of H4TCPP, UiO-66-SO3H and UiO-66-H4TCPP (a) and XRD spectra of UiO-66-SO3H and UiO-66-H4TCPP (b). Figure 5 As can be seen from (a), 1025cm -1 and 1079cm -1 The peak at 1170 cm is due to the stretching vibration of the S=O double bond and the vibration of the n-face skeleton when the hydrogen atoms on the benzene ring are replaced by sulfonic acid groups. -1 The peak at can be attributed to the stretching vibration of O=S=O bond.
[0051] In the AIE molecule H4TCPP, 1726 cm -1 The stretching vibration peak of C=O is 3450cm -1 The vibration peak of OH is at 1726cm. In the UiO-66-H4TCPP molecule, the characteristic peak of sulfonic acid group still exists, but the peak at 1726cm -1 The C=O vibration peak at 100° disappears, proving the successful coordination between the carboxyl group of H4TCPP and the zirconium ion. Figure 5 The X-ray diffraction comparison of UiO-66 and UiO-66-SO3H in (b) shows that the diffraction peak at 8.48° is destroyed due to the introduction of sulfonated terephthalic acid, but the diffraction peaks at 7.36° and 25.68° still exist. Under the action of H4TCPP molecules, its crystal structure has changed and new diffraction peaks have appeared, which confirms the successful synthesis of UiO-66-H4TCPP.
[0052] Figure 6 The X-ray photoelectron spectroscopy (XPS) of UiO-66-SO3H and UiO-66-H4TCPP was further analyzed by XPS. The characterization results are as follows: Figure 6 shown. Figure 6 (a) is the high-resolution Zr 3d XPS spectra of UiO-66-SO3H and UiO-66-H4TCPP. Compared with UiO-66-SO3H, the characteristic peaks of Zr-O bonds of 3d3 / 2 and 3d5 / 2 of UiO-66-H4TCPP at 184.73ev and 182.37ev shifted to the low field, indicating that the coordination environment of Zr changed. This is mainly due to the introduction of new ligand H4TCPP into UiO-66-H4TCPP, forming a new skeleton UiO-66-H4TCPP. The high-resolution C1s XPS spectrum of UiO-66-H4TCPP contains four peaks at 288.35ev, 285.74ev, 284.72ev and 284.20ev, which are C=O / CO, CS, C=C / CC and CN respectively. The existence of the CN characteristic peak strongly confirms the successful synthesis of UiO-66-H4TCPP. Compared with UiO-66-SO3H, the characteristic peak of C1s in UiO-66-H4TCPP shifts to the low field, indicating that the chemical environment of the C atom in UiO-66-H4TCPP has changed. The introduction of H4TCPP leads to an increase in the electron cloud density around it, causing the binding energy to move to the low field.
[0053] Figure 7 Fluorescence emission spectra of different ligand addition mass ratios for synthesizing UiO-66-H4TCPP. In order to further improve the fluorescence performance of UiO-66-H4TCPP, the synthesis conditions of UiO-66-H4TCPP were optimized. The effect of adding different mass ratios of H4TCPP and BDC-SO3H on the fluorescence intensity of UiO-66-H4TCPP was investigated. It can be seen from the fluorescence spectrum that when the mass ratio of H4TCPP to BDC-SO3H is 1:0.8, the fluorescence emission is weak. When the mass ratio of H4TCPP to BDC-SO3H is 1:1, the fluorescence intensity of the material increases significantly. The amount of H4TCPP molecules added is continued to increase. When the mass ratio of H4TCPP to BDC-SO3H is 1:1.4, the fluorescence intensity of the material does not increase significantly.
[0054] Figure 8The SEM images of different ligand mass ratios of the synthesized aggregation-induced emission metal organic framework UiO-66-H4TCPP are shown in Figure 8(a). It can be seen that the morphology of UiO-66 is a regular octahedron with an average diameter of about 100-150nm. When BDC-SO3H is not added, the morphology of Zr-H4TCPP is a regular ellipse with an average diameter of about 150-200nm. As the amount of H4TCPP molecules added increases, the morphology of UiO-66-H4TCPP gradually changes to an ellipse. Combined with the fluorescence emission spectra of the materials with different ligand ratios, the mass ratio of H4TCPP to BDC-SO3H is 1:1, which is the optimal addition amount. The UiO-66-H4TCPP synthesized under this ligand ratio is also selected for the subsequent performance and characterization tests of the material.
[0055] Fig. 9 XRD spectra of different ligand mass ratios of UiO-66-H4TCPP for synthesizing the aggregation-induced emission metal organic framework. From XRD, it can be seen that UiO-66-H4TCPP exhibits a different crystal structure from UiO-66-SO3H. When the mass ratio of H4TCPP to BDC-SO3H is greater than 1:0.8, changing the amount of H4TCPP added has little effect on the crystallinity of UiO-66-H4TCPP. It has diffraction peaks different from those of UiO-66-SO3H at 8.75°, 10.40°, and 11.45°. When the mass ratio of H4TCPP to BDC-SO3H is 1:1, the material has good crystallinity, and the subsequent performance and characterization tests of the material also select UiO-66-H4TCPP synthesized under this ligand ratio.
[0056] Fig.10 The N2 adsorption-desorption isotherms of UiO-66-SO3H and UiO-66-H4TCPP are shown in Figure 2. The specific surface area and pore structure of the material are crucial to the sensing performance of the material, so the N2 adsorption-desorption isotherms of UiO-66-SO3H and UiO-66-H4TCPP were measured. The pore size distribution of UiO-66-SO3H and UiO-66-H4TCPP is mainly in the range of 3-10nm, which belongs to mesoporous materials. The specific surface area and pore volume of UiO-66-H4TCPP range from 117.941m 2 / g, 0.551cc / g down to 63.683m 2 / g, 0.356cc / g. This result is believed to be due to the fact that the introduced AIE molecule H4TCPP occupies the pore structure of the UiO-66-SO3H skeleton. However, the introduction of H4TCPP molecules in MOF is beneficial to the detection of nitrobenzene gas.
[0057] Fig.11The thermogravimetric curves of H4TCPP, UiO-66-SO3H, and UiO-66-H4TCPP. Fig.11 It can be seen that the mass loss of materials UiO-66-SO3H and UiO-66-H4TCPP before 100°C in the first stage can be attributed to the evaporation of water, and the mass loss is 10.76%. The mass loss of material UiO-66-SO3H in the second stage is mainly due to the evaporation of solvent in the MOF pores and the dehydroxylation of zirconium oxygen clusters, with a mass loss of about 22.23%. UiO-66-H4TCPP has two mass losses in this stage, which can be attributed to the evaporation of solvent in the MOF pores and the dehydroxylation of zirconium oxygen clusters and the mass loss of H4TCPP. The material collapsed in the third stage. UiO-66-SO3H began to decompose at 370°C, while the decomposition temperature of UiO-66-H4TCPP was 500°C. It can be seen that the introduction of H4TCPP molecules has a good improvement in the thermal stability of the material.
[0058] Fig.12 To characterize the aggregation-induced luminescence performance of the aggregation-induced luminescence metal organic framework UiO-66-H4TCPP, (a) and (c) are the fluorescence spectra of H4TCPP and UiO-66-H4TCPP in different aggregation states; (b) and (d) are the change curves of the fluorescence intensity of H4TCPP and UiO-66-H4TCPP in different aggregation states. DMF is a good solvent for H4TCPP and UiO-66-H4TCPP, and H2O is a poor solvent for H4TCPP and UiO-66-H4TCPP. It can be seen from the figure that with the increase of H2O content, the fluorescence intensity of H4TCPP and UiO-66-H4TCPP also gradually increases. This is mainly because in poor solvents, the material is more inclined to form aggregates, which restricts the molecular motion and releases energy in the form of fluorescence. When H2O / DMF is 1:1, the material has the maximum fluorescence intensity; for the UiO-66-H4TCPP molecule, when H2O / DMF is 9:1, the material has the maximum fluorescence intensity.
[0059] Fig.13 The UV-visible absorption spectra (a) and optimal excitation / emission spectra (b) of H4TCPP, UiO-66-SO3H, and UiO-66-H4TCPP. Fig.13(a) It can be seen that compared with the ultraviolet absorption peaks of H4TCPP and UiO-66-SO3H, the maximum ultraviolet absorption peak of UiO-66-H4TCPP has a significant blue shift. The shift of the absorption peak indicates that the coordination environment of the Zr element has changed, which further proves that H4TCPP may have a coordination effect with the central metal ion in UiO-66-SO3H, proving the formation of the UiO-66-H4TCPP metal organic framework.
[0060] Example 3: Recognition of nitrobenzene by aggregation-induced emission metal organic framework UiO-66-H4TCPP
[0061] Test solution preparation: Take 20 mg of UiO-66-H4TCPP prepared in Example 2, dissolve it in 20 mL of deionized water, and disperse it evenly by ultrasonic to obtain a probe dispersion with a concentration of 1 mg / mL.
[0062] Detection of nitrobenzene solution: Prepare nitrobenzene stock solution with a concentration of 0.01 mol / L, then dilute it to 0-200 nM, add 100 μL of the diluted nitrobenzene solution of different concentrations into 5 mL, 1 mg / mL probe solution, and then perform fluorescence test.
[0063] Detection of nitrobenzene gas: The detection of nitrobenzene gas is carried out in a homemade 18L closed container. The nitrobenzene solution is injected into the container through the small hole with a rubber plug on the top of the device with a syringe. The heating device in the container will evaporate the nitrobenzene solution into gaseous nitrobenzene. 15mg of UiO-66-H4TCPP is placed in the above closed container and taken out after 20 minutes for solid fluorescence test. The concentration of nitrobenzene gas can be calculated by the ideal gas state equation pV=nRT.
[0064] Fig.14 The response of UiO-66-H4TCPP after detecting different aromatic compounds and volatile organic compounds formaldehyde, 1-Butanol, EtOAc, Ph-Cl, Benzene, Toluene, Isopropyl alcohol, o-Xylene, Styrene, NB (a) and its fluorescence intensity change bar graph (b). Fig.14 (a) It can be seen that after the material detects 500nM nitrobenzene, the fluorescence intensity of the material will decrease significantly, proving that UiO-66-H4TCPP can detect nitrobenzene with high sensitivity. Fig.14 As shown in (b), UiO-66-H4TCPP has good selectivity for nitrobenzene.
[0065] Fig.15 The response of UiO-66-H4TCPP to different aromatic compounds and volatile organic compounds at 0-200nM (a) and the anti-interference of UiO-66-H4TCPP in detecting nitrobenzene (b). Considering the complexity of the actual environment, and further considering other potential interferents that may exist when UiO-66-H4TCPP detects nitrobenzene, in the presence of formaldehyde, n-butanol, ethyl acetate, chlorobenzene, benzene, toluene, isoamyl alcohol, xylene, styrene, etc., UiO-66-H4TCPP still has a good fluorescence quenching response to nitrobenzene. The above results show that UiO-66-H4TCPP has satisfactory anti-interference in the detection of nitrobenzene.
[0066] Fig.16 The fluorescence emission spectrum of the probe response after adding 0-200 nM nitrobenzene solution (a) and the linear relationship between the probe fluorescence intensity and nitrobenzene concentration (b). Fig.16 As shown in (a), as the concentration of nitrobenzene increases, the fluorescence intensity of the probe gradually decreases. Fig.16 As shown in (b), the fluorescence intensity of the sensing system has a good linear relationship with the nitrobenzene concentration in the range of 20-200 nM, R 2 =0.99111, the detection limit is calculated by the formula D=3σ / K (σ is the standard deviation of the fluorescence intensity of the fluorescent material UiO-66-H4TCPP itself, the number of measurements is not less than 20 times, K is the coefficient of variation of the fluorescence intensity when the fluorescent material UiO-66-H4TCPP detects nitrobenzene solution). The detection limit of this fluorescent probe for nitrobenzene is as low as 2.71nM.
[0067] Fig.17 The fluorescence emission spectrum of UiO-66-H4TCPP after detecting 0-50ppm nitrobenzene gas (a) and the linear relationship between the probe fluorescence intensity and nitrobenzene gas concentration (b). Fig.17 As shown in (a), as the concentration of nitrobenzene gas increases, the fluorescence intensity of the probe gradually decreases. Fig.17 As shown in (b), the fluorescence intensity of the sensing system has a good linear relationship with the nitrobenzene concentration in the range of 5-50 ppm, R 2 =0.99289, the general formula D=3σ / K (σ is the standard deviation of the fluorescence intensity of the fluorescent material UiO-66-H4TCPP itself, the number of measurements is not less than 20 times, K is the coefficient of variation of the fluorescence intensity when the fluorescent material UiO-66-H4TCPP detects nitrobenzene gas) calculates that the detection limit of the fluorescent probe for nitrobenzene gas is as low as 4.11ppm.
[0068] Fig.18The response time and cycle performance of UiO-66-H4TCPP for nitrobenzene detection are shown in Figure 1. The material can complete the detection of 50nM and 100nM nitrobenzene within 8 minutes, proving that the material can achieve rapid detection of nitrobenzene. At the same time, the cycle performance of UiO-66-H4TCPP for nitrobenzene gas detection was tested. After UiO-66-H4TCPP detected 20ppm nitrobenzene gas, it was heated at 200℃ for 30min, which allowed the nitrobenzene gas in the pores of the material to be separated under heating conditions. After completing five cycles, the fluorescence intensity of the material only lost 5.9%, proving that the material has good cyclic performance.
[0069] Example 4 Preparation of UiO-66-H4TCPP@PVDF film
[0070] Preparation of UiO-66-H4TCPP@PVDF film: Add 200 mg PVDF to 2 mL DMF solution, heat at 70°C until PVDF is completely dissolved, take 60 mg UiO-66-H4TCPP powder prepared in Example 2, add it to the PVDF solution, stir evenly and pour it on a glass mold, then place it in deionized water, the UiO-66-H4TCPP@PVDF film can be detached from the glass mold, and a flexible aggregation-induced luminescence film that can detect nitrobenzene can be obtained.
[0071] Detection of nitrobenzene gas: The detection of nitrobenzene gas is carried out in a homemade 18L closed container. The nitrobenzene solution is injected into the container through the small hole with a rubber plug on the top of the device with a syringe. The heating device in the container will evaporate the nitrobenzene solution into gaseous nitrobenzene. The UiO-66-H4TCPP@PVDF film is placed in the above closed container and taken out after 20 minutes for solid fluorescence test. The concentration of nitrobenzene gas can be calculated by the ideal gas state equation pV=nRT.
[0072] Fig.19 The actual photo and optical photo of the flexible UiO-66-H4TCPP@PVDF film prepared by blending the aggregation-induced emission metal organic framework UiO-66-H4TCPP with polyvinylidene fluoride (PVDF) for portable detection of nitrobenzene gas under 365nm ultraviolet light. The UiO-66-H4TCPP@PVDF film is white in appearance and exhibits blue fluorescence emission under 365nm ultraviolet light, which is mainly due to the blue fluorescence of the introduced UiO-66-H4TCPP molecules.
[0073] Fig. 20The linear relationship between the actual photo of UiO-66-H4TCPP@PVDF film after detecting 0-50ppm nitrobenzene gas and the concentration of nitrobenzene gas. In order to achieve portable detection of nitrobenzene gas, UiO-66-H4TCPP@PVDF film was prepared, and the detection ability of UiO-66-H4TCPP@PVDF film for nitrobenzene gas was tested. When the concentration of nitrobenzene gas increased from 0 to 50ppm, the fluorescence intensity of the film was gradually quenched. Fig. 20 (a) is a photo of the UiO-66-H4TCPP film after detecting 0-50ppm nitrobenzene gas. Fig. 20 (b) and (c) are the fluorescence intensity change curves and linear relationships, y = 0.01595c + 1.10278, R 2 =0.91935.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An aggregation-induced emission metal-organic framework, characterized in that: The preparation method is as follows: ZrCl4 is dissolved in an N,N-dimethylformamide solution and carried out under ultrasonic conditions. Subsequently, BDC-SO3H and AIE molecule H4TCPP are added, and then treated under ultrasonic conditions to obtain a transparent solution. A certain amount of acetic acid is added to the solution, and the mixed solution is placed in a polytetrafluoroethylene reactor for heating and reaction. After the reaction is completed, the aggregation-induced emission metal organic framework material UiO-66-H4TCPP can be obtained by centrifugal washing.
2. The aggregation-induced emission metal-organic framework according to claim 1, characterized in that: The preparation method of H4TCPP is as follows: vitamin B1 is added to a mixed solvent of CH3OH and H2O, the pH is adjusted to 9-10, methyl 4-toluate is added, the reaction mixture is stirred in an ice-water bath for 1 hour, heated to form a precipitate, and filtered to obtain a product, acetic anhydride is added to a solution of the product and ammonium acetate, stirred at 120°C and N2 for 12 hours to obtain a solid product, filtered and washed with water and diethyl ether to obtain a yellow solid 2,3,5,6-tetrakis(4-(methoxycarbonyl)phenyl)pyrazine; NaOH is added to 2,3,5,6-tetrakis(4-(methoxycarbonyl)phenyl)pyrazine in a THF-H2O solution, the mixture is refluxed for about 12 hours, tetrahydrofuran is evaporated, the pH is adjusted to 4-5, the precipitate is filtered and washed with water to obtain a yellow solid H4TCPP.
3. The aggregation-induced emission metal-organic framework according to claim 2, characterized in that: The heating is heating at 60°C for 1 hour and heating at 85°C for 1 hour.
4. The aggregation-induced emission metal-organic framework according to claim 1, characterized in that: The mass ratio of BDC-SO3H to ZrCl4 is 0-0.67:1, and the mass ratio of BDC-SO3H to H4TCPP is 1:0-1.
4.
5. The aggregation-induced emission metal-organic framework according to claim 1, characterized in that: The heating reaction is carried out at 0-120°C for 0-24h.
6. Use of an aggregation-induced emission metal organic framework according to any one of claims 1 to 5 in fluorescent detection of nitrobenzene in water, characterized in that: Here is how: 1) Add 1 mg / mL UiO-66-H4TCPP solution to a solution containing 0-200 nM nitrobenzene, and perform fluorescence test to obtain a linear relationship between nitrobenzene concentration and fluorescence intensity, y=0.04710c+1.09875, R 2 =0.99111; 2) Add 1 mg / mL UiO-66-H4TCPP solution to the nitrobenzene solution to be tested, and perform a fluorescence test. Substitute the fluorescence intensity into the linear equation obtained in step 1) to calculate the concentration of nitrobenzene in water.
7. The use of an aggregation-induced emission metal organic framework in fluorescence detection of nitrobenzene gas according to claim 1, characterized in that: Here is how: 1) In a sealed container, 15 mg of UiO-66-H4TCPP powder was placed, and nitrobenzene was volatilized by heating to generate 0-50 ppm nitrobenzene gas in the device. After 20 minutes, the solid powder material was taken out and solid fluorescence test was performed to obtain the linear relationship between nitrobenzene gas concentration and fluorescence intensity, y=0.03108c+0.85508, R 2 =0.99289; 2) Put 15 mg of UiO-66-H4TCPP powder in a sealed container, place the nitrobenzene gas to be tested in a sealed device, take out the solid powder material after 20 minutes, and perform a solid fluorescence test. The concentration of nitrobenzene gas can be calculated based on the fluorescence intensity, the linear equation obtained in step 1) and pV=nRT.
8. A portable UiO-66-H4TCPP@PVDF film for detecting nitrobenzene gas, characterized in that: PVDF is added to the DMF solution and heated until the PVDF is completely dissolved. The UiO-66-H4TCPP powder according to any one of claims 1 to 5 is added to the PVDF solution, stirred evenly and poured onto a glass mold, which is then placed in deionized water. The UiO-66-H4TCPP@PVDF film is separated from the glass mold to obtain a UiO-66-H4TCPP@PVDF film for portable detection of nitrobenzene gas.
9. The UiO-66-H4TCPP@PVDF film for portable detection of nitrobenzene gas according to claim 8, The mass ratio of UiO-66-H4TCPP to PVDF was 0.2:1, and the heating reaction was carried out at 70°C for 0-30 min.
10. The UiO-66-H4TCPP@PVDF film for portable detection of nitrobenzene gas according to claim 8 or 9, characterized in that: The method is as follows: a UiO-66-H4TCPP@PVDF film is placed in a sealed container, nitrobenzene is heated and volatilized to produce 0-50 ppm nitrobenzene gas in the device, and the film is taken out after 20 minutes. Under a 360nm ultraviolet lamp, it can be observed that the blue fluorescence of the film is effectively quenched.
Citation Information
Cited By
Colorimetric / fluorescent dual-mode nano-enzyme sensor, preparation method thereof and application of colorimetric / fluorescent dual-mode nano-enzyme sensor in formaldehyde detection
CN120992600A
A colorimetric / fluorescent dual-mode nanozyme sensor, a preparation method thereof and application thereof in formaldehyde detection
CN120992600B